Older peoples' experiences of informal support after giving up driving. (March 2019) - Murray, Amy; Musselwhite, Charles
Abstract: Using a phenomenological approach, this study explored people who have given up driving's experiences of informal support following driving cessation based upon individual, semi-structured in-depth interviews with seven individuals who had retired from driving (n = 7). Findings highlight the complex nature of informal support as an alternative to driving in later life for older adults, showing there is no clear cut, linear process which occurs relating to this type of support. Retired older driver's experiences of informal support are multi-faceted, which include a broad range of practical and psychosocial factors. Informal support was usually provided in very practical terms but the receiver would often also need psychosocial and social support. Motivation for informal support stemmed from ill health, health concerns and was often coupled with living in an area with poor bus service. It was common for the participants to feel a burden on others and use strategies to reduce that feeling including rationing, trip chaining and providing reciprocation through gifts. The findings suggest the need for novel interventions which recognise the changing face of informal support, ensuring this is not the only viable alternative to driving in later life. Highlights: The nature of informal support for people who retire from driving is under researched. This study looks in-depth at 7 retired drivers' experiences of using informal support. Informal practical and emotional support is important for people who give up driving. Informal support is most needed for retired drivers those who suffer ill health and live away from bus routes. People can feel a burden when they rely on informal support, so they ration it, reciprocate and trip chain.